SIFAT PAPAN PARTIKEL DARI LIMBAH EKSPLOITASI - Rozak Memed; I M Sulastiningsih (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
The result of a study on the properties of particle board made from logging waste is reported in this paper. The wood species used in the study as raw material for particle board are meranti (Shorea sp.), ramin (Gonystylus bancanus Kurz.) and combination of the two species. The result shows that wood species and particle size has a significant effect on the water absorption and thicknessswelling of particle board. Bending strength (MOR) of particle board is only affected by wood species, while Modulus of elasticity, internal bond and shear strength are not affected by wood species and particle size. In general the physical and mechanical properties of particle board studied meet the FAO standard for low density particle board.